PENINGKATAN PENDAPATAN : FAKTOR PENGGUNA E – COMMERCE DAN FINANCIAL TECHNOLOG - Fastabiqul Khoiroh; Chairil Anwar (Jurnal Riset Akuntansi, 2025)
MSMEs play a strategic role in Indonesia's economy, particularly in job creation and improving societal welfare. The rapid digital transformation encourages MSMEs to utilize e-commerce and financial technology to increase their income. This study aims to analyze the impact of e-commerce and financial technology usage on the income growth of MSMEs in Sidoarjo Regency. Using a quantitative correlational approach, data was collected from 100 MSME respondents through a Likert-scale-based questionnaire. Regression analysis results indicate that e-commerce significantly influences MSME income growth, whereas financial technology has not shown a significant impact. These findings suggest that business digitalization through e-commerce is more effective in enhancing MSME income compared to financial technology adoption. Therefore, increasing digital literacy, particularly in financial technology, is necessary to help MSMEs optimize their use of financial technology in business management. Keywords: MSMEs, E-Commerce, Financial Technology, Income, Digitalization